PENDAMPINGAN PENGGUNAAN APLIKASI CORETAX UNTUK MENINGKATKAN LITERASI PERPAJAKAN BAGI PELAKU UMKM DI KOTA SERANG - Ibrohim Ibrohim; Surachman Surachman (Yayasan Education and Social Center, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic growth and employment creation. However, many MSME actors still face limitations in understanding tax regulations and utilizing digital tax administration services. The implementation of the Core Tax Administration System (Coretax) by the Directorate General of Taxes requires taxpayers, including MSME actors, to adapt to digital-based tax services. This Community Service Program aimed to improve tax literacy among MSME actors in Serang City through assistance in using the Coretax application. The program was conducted for one month in January 2026 using participatory and educational approaches through socialization, tax education, direct demonstrations, practical training, and technical assistance. A total of 30 MSME actors participated in the activities. The results indicated a significant improvement in participants' understanding and skills in using Coretax. Understanding of Coretax functions increased from 36.67% to 86.67%, while understanding of digital tax reporting increased from 26.67% to 80.00%. Participants were also able to perform account activation, create billing codes, manage tax profiles, and conduct digital tax reporting independently. Therefore, the mentoring program effectively improved tax literacy and supported the acceleration of digital transformation in tax administration among MSME actors in Serang City.